Heimliche Stallaufnahmen aus gesellschaftlicher Sicht im Wechselspiel zwischen Landwirtschaft, Tierschutzorganisationen und staatlichen Kontrollmechanismen; A Public Perspective of Undercover Investigations in Animal Husbandry - an Interaction between Agriculture, Animal Welfare Organizations and Governmental Control - Maureen Schulze; Antje Risius; Achim Spiller (German Journal of Agricultural Economics (GJAE), 2018)
– Undercover investigations in animal husbandry have attracted great media attention in recent years. Animal welfare organizations, farmers and politi-cians have been discussing the need for undercover investigations and their consequences for animal activists. Since the public perspective and its influencing factors had not previously been scientifically investigated an exploratory study with 292 German consumers is conducted. Using structural equation modeling the attitude to undercover investigations and their influencing factors are revealed. Generally the results show a positive attitude towards undercover investigations. They are perceived as necessary for animal welfare reasons because state-owned control mechanisms are unsatisfactory. In addition, the results show that the work of responsible animal welfare organizations receives social approval and the public is unsure about the psychological burden on affected farmers. The positive attitude towards undercover investigations is influenced by the increasingly critical view on livestock farming. However, the public rejects harsher punishment of investigators. Undercover investigations demonstrate the discrepancy between agriculture and society and show that the welfare of farm animals is becoming increasingly important.
Keywords: 330